Microbial mineralization combined with vegetation soil stabilization in coal mining subsidence areas - Ying GAO; Tao LI; Kaidan ZHENG; Limin FAN; Ruhong BAI; Qiang SUN (Meitan kexue jishu)
The shallow geological environment of coal mining in ecologically fragile mining areas continues to deteriorate. In order to control soil instability and soil erosion in collapsed areas, experimental research on microbial mineralization combined with vegetation soil stabilization was carried out in coal mining collapsed areas. Based on the ecologically fragile Yushuwan coal mine 20107 working face as the research background, an experimental study was conducted on the impact of MICP on vegetation, specifically testing the effects of MICP solidification on vegetation growth, soil nutrients, and vegetation root growth, based on coal mining subsidence, ground fissures, and physical and chemical observations of mining soil; We conducted an experiment on the influence of MICP combined with vegetation roots on the shear strength of mining disturbed soil, specifically comparing and testing the effects of different root lengths, root dosages, and bacterial gum ratios on soil shear strength; Based on the scanning electron microscopy observation of MICP solidified soil under different working conditions and the results of MICP calcium carbonate production testing, the law of composite restoration of soil in collapsed areas was explained. The research results indicate that: ① Coal mining has the most significant impact on soil moisture content, with a 7.7% decrease in moisture content in the severely disturbed area (D1) compared to the slightly disturbed area (D0). The effect of soil pH value is not significant, while the organic matter content, total nitrogen content, available phosphorus content, and available potassium content in the soil are in descending order: D0, D2 (generally disturbed fractured zone), D3 (generally disturbed non fractured zone), and D1; ② The effect of MICP on vegetation growth can be divided into two stages: in the first stage (1−2 weeks), MICP mainly plays a role in inhibiting vegetation growth. Potted plants without MICP solidification have an average height of 7.4% to 47.7% higher than those with MICP solidification; In the second stage (3−4 weeks), MICP mainly plays a role in promoting vegetation growth. Potted plants without MICP solidification have an average height 23.7%−32.3% lower than those with MICP solidification; The growth of vegetation roots and soil physicochemical indicators verified the promoting effect of MICP on vegetation after 4 weeks; ③ The addition of root system without MICP solidification increased the cohesion and internal friction angle of solidified soil by 42.1% and 10.6%, respectively. The addition of root system with MICP solidification increased the cohesion and internal friction angle of solidified soil by 62.3% and 19.4%, respectively. The optimal parameters for joint solidification of the two are: root length of 5−10 cm, root addition ratio of 0.8%, and bacterial gum ratio of 1∶1.5 During the solidification process of MICP, the production of calcium carbonate D1>D2>D3 indicates that the more severe the coal mining disturbance, the higher the degree of MICP intervention and repair. This study provides experimental reference for soil stabilization engineering in coal mining subsidence areas of ecologically fragile mining areas.